Effects of Ludotechnical Model in technical learning, competence and motivation when teaching basketball in Physical Education - Rubio-Castillo, A. D.; Gómez-Mármol, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
This research analyzes the effect of Ludotechnical Model on technical learning, competence and motivation when teaching basketball. With that aim, a seven-lessons-teaching unit was implemented to 46 scholars aged between 16 and 17 years old. Next questionnaires were used to data collection: motor competence Test AMPET (AMPETe-R) by Ruiz-Pérez, Moreno-Murcia, Ramón-Otero and Alias-García (2015), Sport perceived motivation adapted to Physical Education (PMCSQ-2) by González-Cutre et al. (2008) and an observation tool ad hoc designed to technical learning. Results show that there are not significant differences in motivation and self perceived competence levels meanwhile, in technical learning variable, differences have been appreciated indeed, in all technical movements, especially in “defense position”. This research concludes that Ludotechnical Model can be considered as an adequate alternative to traditional methodology although keeping on developing new intervention researches is required.